Platelet Rich Plasma PRP in Dental and Oral Surgery: Wound Healing to Bone Regeneration - Syed Akbar Abbas Zaidi, Bushra Arain, Nosheen Khawar, Sana Adeeba Islam, Alvina Ali Shaikh, Syed Aijaz Ali Zaidi, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The aim of this study to evaluate the outcome of the efficacy of the PRP use to promote wound healing and bone regeneration. Study design: The study was cross sectional being conducted in the department of Dentistry, Bahria University Dental College, Karachi six months from June 2022 to November 2022. Methods: A total number of the participants were 150. The male and female genders were both included who suffered dental surgery. The sample of blood was taken around 55cc by a trained medical expert. After that, blood will be centrifuged to separate the platelet-rich plasma from the remaining components of your blood. For the greatest results, your blood will often be spun two to three times. Results: The age range was 20-60 years and > 61 years old, with an average of 51.1±12.5 years, which indicate highly significant tooth loss at above 61 years old age p<0.005**. The PRP treatment was showing significant improvement in the dental and oral postoperative treatment p<0.005. After postoperative analysis of the participants by the treatment of PRP, which show significant improvement CAL, gingival recession, repair bone defect, stop tooth extraction and root coverage show significant result <0.005** as compared to control group. Conclusions: Following tooth extraction, the application of PRP in the alveolar socket can improve soft tissue healing and favorably affect bone regeneration. Root lengthening, apex closure, and dentin wall thickening were all higher, and they all encourage the rejuvenation of the pulp tissue and further root development. Keywords: Platelet rich plasma, cytokine, growth factor and blood.